2019
DOI: 10.4269/ajtmh.18-0365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supportive Supervision on Competency of Febrile Clinical Case Management in Sub-Saharan Africa

Abstract: Since 2010, the WHO has recommended that clinical decision-making for malaria case management be performed based on the results of a parasitological test result. Between 2015 and 2017, the U.S. President's Malaria Initiative-funded MalariaCare project supported the implementation of this practice in eight sub-Saharan African countries through 5,382 outreach training and supportive supervision visits to 3,563 health facilities. During these visits, trained government supervisors used a 25-point checklist to obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…MalariaCare's experience has indicated that supportive supervision, in the context of a comprehensive QA system, builds, improves, and maintains performance over time, as demonstrated in other studies from the project. [12][13][14] For a wellstructured OTSS to be effective and efficient, host governments and other implementing partners should develop the following when implementing supportive supervision: 1) a checklist that balances data collection with the primary objective of mentoring; 2) criteria for supervisor selection coupled with ongoing evaluation; 3) a dynamic strategy for facility selection and criteria to determine the continued need for support and the type of support; 4) criteria for selecting facilities to conduct OTSS and determine the appropriate frequency of visits; and 5) a system that enables the analysis of supportive supervision data for decision-making. Ensuring the quality of supervision schemes through these methods can be cost-and human resource-intensive.…”
Section: Resultsmentioning
confidence: 99%
“…MalariaCare's experience has indicated that supportive supervision, in the context of a comprehensive QA system, builds, improves, and maintains performance over time, as demonstrated in other studies from the project. [12][13][14] For a wellstructured OTSS to be effective and efficient, host governments and other implementing partners should develop the following when implementing supportive supervision: 1) a checklist that balances data collection with the primary objective of mentoring; 2) criteria for supervisor selection coupled with ongoing evaluation; 3) a dynamic strategy for facility selection and criteria to determine the continued need for support and the type of support; 4) criteria for selecting facilities to conduct OTSS and determine the appropriate frequency of visits; and 5) a system that enables the analysis of supportive supervision data for decision-making. Ensuring the quality of supervision schemes through these methods can be cost-and human resource-intensive.…”
Section: Resultsmentioning
confidence: 99%
“…Across country programs where OTSS was implemented using EDS, MalariaCare has observed improvements in each of the project's six key indicators (RDT, microscopy and clinical performance, testing before treatment, and adherence to positive and negative test results). [15][16][17] Comparing only the operational costs for data entry, EDS tended to be more expensive per visit than using a paper checklist, with cost differentials ranging from between US $0.16 and US$28.04 per visit for five of the seven countries. The EDS operational costs were lower when it was used at scale-when there were a greater number of health facilities over a greater number of visits, when health facilities were visited by fewer supervisors, and when tablets were purchased in bulk.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of introducing the EDS was to improve both supervision data quality and data use, and, ultimately, to improve the quality of case management of febrile illnesses. The combined effects of OTSS and EDS on the quality of malaria case management are presented in Eliades et al, Alombah et al, and Martin et al [15][16][17] The outcomes presented here focus on the effect of the EDS on data quality and data use.…”
Section: Methodsmentioning
confidence: 99%
“…For example, pregnant women screening for HIV increased significantly from the second visit in Nigeria [16], and the consistency in pneumonia case management improved from 38 to 78 percent between the first to fourth supportive supervision in Ethiopia [7]. For malaria case management, the adjusted regression analysis showed that clinical performance against the checklist improved by an estimated six percentage point by the third visit [19]. Progress on most care steps for malaria case management were observed by having only one visit.…”
Section: Plos Onementioning
confidence: 99%